CENTROID-MOMENT TENSOR SOLUTIONS FOR JULY-SEPTEMBER, 1984 - Dziewonski, A; Franzen, J; Woodhouse, J (1985)
Centroid-moment tensor solutions are presented for 197 earthquakes that occurred during the third quarter of 1984. The solutions are obtained using corrections for aspherical Earth structure. © 1985.